PREJUDICES AND STEREOTYPES IN MULTICULTURAL SOCIETY IN RICHARD LAGRAVENESSE'S FREEDOM WRITERS MOVIE (2007);A SOCIOLOGICAL APPROACH - PRASETYAWATI, SANTI (2011)
This study is aimed to show prejudices and stereotype in multicultural society in Freedom Writers movie by using sociological approach. It is done by establishing three objectives: the first is analyzing the movie based on American society at the twentieth to twenty-first century. Second is analyzing the movie based on its structural elements and the third is analyzing the movie based on the Sociological Approach. This research is qualitative research. Type of data of the study is text and image taken from two data sources: primary and secondary. The primary data source is the Freedom Writers movie directed by Richard LaGravenesse released in 2007. While the secondary data sources are other materials taken from books, journals, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusions. First, based on the structural analysis of each element, it shows that the character and characterization, casting, plot, setting, point of view, theme, mise en scene, cinematography, sound, and editing are related to each other and form unity. Second, based on the Sociological analysis, it is the phenomena in American society in the twentieth to twenty-first century when the riots happen in 1992 that make gang‟s violence and racial tension reach an all time. It is caused the struggle of human right and the badness to follow the prejudice and stereotype in children‟s life.